Mass wasting triggered by seasonal CO2 sublimation under Martian atmospheric conditions: Laboratory experiments. Issue 24 (21st December 2016) - Sylvest, Matthew E.; Conway, Susan J.; Patel, Manish R.; Dixon, John C.; Barnes, Adam
Abstract: Sublimation is a recognized process by which planetary landscapes can be modified. However, interpretation of whether sublimation is involved in downslope movements on Mars and other bodies is restricted by a lack of empirical data to constrain this mechanism of sediment transport and its influence on landform morphology. Here we present the first set of laboratory experiments under Martian atmospheric conditions which demonstrate that the sublimation of CO2 ice from within the sediment body can trigger failure of unconsolidated, regolith slopes and can measurably alter the landscape. Previous theoretical studies required CO2 slab ice for movements, but we find that only frost is required. Hence, sediment transport by CO2 sublimation could be more widely applicable (in space and time) on Mars than previously thought. This supports recent work suggesting CO2 sublimation could be responsible for recent modification in Martian gullies. Key Points: We report the first experiments that demonstrate mass wasting triggered by CO2 sublimation under Martian atmospheric conditions Failures in the absence of slab ice imply a broad applicability of CO2 sublimation for triggering slope movements on Mars Triggering of significant sediment movement by CO2 sublimation suggests involvement in the evolution of Mars gullies and slope streaks